Perceptions and attitudes of dental hygienists toward radiation safety and protection in the Republic of Korea - Yun, Kwidug; Lee, Kyung-Min; An, Seo-Young; Yoon, Suk-Ja; Jeong, Ho-Gul; Lee, Jae-Seo (International journal of oral biology, 2021)
To investigate the perceptions and attitudes of dental hygienists toward radiation safety management in Korea. A total of 800 dental hygienists were randomly selected for an anonymous survey, and 203 of them participated. The questionnaire items included the following: sex, career period, type of installed radiographic equipment, recognition of the diagnostic reference level (DRL), participation in radiation safety education, and attitudes toward radiation protection for both patients and dental hygienists. The participants were divided into two groups according to their years of experience (< 10 years versus ≥ 10 years). The difference between the groups was investigated according to frequency distribution. Fisher’s exact test or Pearson’s chi-square (χ2) test was used as appropriate. A regression analysis was performed to investigate the impact of wearing a thyroid collar for personnel protection during patient radiation exposure. The types of installed radiographic equipment included panoramic radiography (96.1%), cephalometric radiography (76.9%), intraoral radiography (72.9%), and cone-beam computed tomography (69.5%). Significant differences were observed in the learning pathway for the DRL (Fisher’s exact test, p < 0.05), satisfaction with radiation safety education (Pearson’s χ2 test = 5.3975, Pr = 0.02), and use of personnel radiation monitoring systems (Pearson’s χ2 test = 18.1233, Pr = 0.000) between the groups. Significant differences were also observed in personnel protection using a thyroid collar and patient protection during panoramic radiography (odds ratio = 14.2). Dental hygienists with more than 10 years of experience were more satisfied with radiation safety education and more interested in radiation monitoring. Considering career experience, customized, continuous, and effective radiation safety management education should be provided.